Pain Intensity among Women with Post-Caesarean Section: A Descriptive Study - Marfuah, Dewi; Nurhayati, Nunung; Mutiar, Astri; Sumiati, Mimin; Mardiani, Rani (KnE Life Sciences, 2019)
Background: The frequency of Caesarean section increased from 5% to 15% across the world. According to statistics, it is highest in the U.S. or around 24%, and then in Canada about 20%, in Denmark about 13%, 10% in England, and it is lowest in Japan 7%. Post-cesarean section women experience pain due to operative trauma. Individual variability of postoperative pain is inﬂuenced by multiple factors, including sensitivity to pain, psychological factors, age, and genetics. Cesarean delivery patients have even more compelling reasons to achieve optimal postoperative pain relief than other surgical patients, but they also present unique challenges. Post cesarean delivery patients are at a higher risk for thromboembolic events, which may also be precipitated by immobility from inadequate pain control or excessive sedation from opioids. Objectives: This research aimed to describe pain intensity among women with post-cesarean Section. Methods: This research conducted at an obstetric ward in Hasan Sadikin Hospital, Bandung, West Java, Indonesia with 60 women with postcesarean section. Instrument used Visual Rating Scale (VAS) for pain measurement. A descriptive Study with Mean±SD for univariate analysis Result: Pain intensity among women with post-caesarian section were mild pain level with mean of pain level was 2.8. Women with mild pain level as much as 81,6%. Conclusions: As a nurse, can be considered as a nonpharmacological intervention to reduce the pain of cesarean section effectively and to decrease the number of medications and their side effects.